Steps to Success: the Dynamics of Career Self-Efficacy in Working Students - Ramadlan, Raynal Fira; Rahmawati, Ajeng Intan Nur; Permatasari, Devi (International Journal of Business, Law, and Education, 2025)
Career Self-Efficacy is an individual's belief in their ability to plan and achieve career goals, which is crucial as it can influence students' academic achievement and future planning. This study aims to gain an in-depth understanding of the dynamics of Career Self-Efficacy in a student who maintains academic achievement while also working. The research employs a qualitative approach with an intrinsic case study design, and the sampling technique used is purposive sampling, with the subject identified as D.Z or N. The research was conducted at N's home in Banyuanyar Tengah Village and at SMPN 2 Gending. Data were collected through semi-structured interviews, participant observation, and documentation, and analyzed using Miles & Huberman’s interactive analysis model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the subject’s Career Self-Efficacy is shaped through the interaction of various factors such as interest, motivation, self-regulation, environmental support, personal aspirations, self-determination, and habits, all of which serve as learning experiences. The subject is able to maintain academic performance and has a clear career direction thanks to high self-efficacy, adaptive strategies in facing challenges, and strong support from family and school. This study recommends further exploration of Career Self-Efficacy dynamics in students from diverse economic backgrounds and types of employment